Effect of a mixture of botanicals extracts plus mannitol on hydration and bloating sensation. An open label study in women with high extra cellular water. Issue 17 (1st September 2020) - Perna, Simone; Biserni, Manuela; Borsani, Filippo; Berardi, Martina; Spadaccini, Daniele; Rondanelli, Mariangela
Abstract: The aim of the study is to evaluate the effectiveness of of 4 and 8 week supplementation with highly standardized formula with Fraxinus ornu s L ., plus Ananas comosus L., concentrated juice, Betula pendula R., Equisetum arvense L., Urtica dioica L. and Pilosella officinarum L. Vail dry extract, on the state of hydration and bloating sensation in subjects with high and moderate extra cellular water (ECW). 19 women (mean age 35 yr and Body Mass Index 22.82 kg\m 2 ) with Extra Cellular Water over 45%completed the study and their data were analysed at baseline, at 30 and 60 days. Bio-impedance, SF36 and anthropometric parameters were assessed. The ECW decreased of −1.97% (at 30 days) and −2.30% (60 days) ( p  < 0.01). Also fat mass decreased of −1.58% (at 30 days) and −2.21% (60 days) ( p  = 0.057). An improvement of free fat mass was assessed ( p  < 0.05) but not on bloating sensation questionnaire at 60 days ( p  = 0.422). Abstract :